Glycolysis control - Feigenson, Gerald W. (Henry Stewart Talks, 2020)
Control of glycogen breakdown (hormonal and local), Hormone amplification, Control of 3 key enzymes of glycolysis, Universal principles of enzyme regulation
Reviewed at 2022/11/27